Сравнительный анализ этапов и методов осуществления геноцида армян в Османской империи и Руандийского геноцида - Armen Marukyan (Banber Arevelagitut'yan Instituti, 2025)
In genocide studies, for a more comprehensive, objective study of genocide committed against victim groups, the method of comparative analysis is used, which allows to identify both similarities and features between different examples of this crime. In the framework of the article, a comparative analysis of the stages and methods of the Armenian-Tutsi genocides was made. The choice of the Rwandan genocide as a subject of comparison with the Armenian Genocide is due to the fact that, unlike the organizers of the Armenian Genocide in the Ottoman Empire, who were convicted by Turkish military tribunals, the organizers of the Tutsi genocide in Rwanda were prosecuted by the International Tribunal, created by the UN Security Council in 1994. Revealing the similarities between the stages and methods of committing two identical crimes will provide an opportunity to reveal the precedent of condemning the Rwandan Genocide in the International Tribunal and the possibilities of applying it to the Armenian Genocide case in the future in an international court. As a result of the comparative analysis of the stages of the two genocides, the methods of implementation, in addition to many similarities, significant differences were registered, from which we have separated the following: 1. In order to end the Armenian Genocide, the Turkish authorities chose the period of World War II, when influential world politicians were engaged in hostilities on different fronts of the war and they would not be able to intervene and prevent its implementation, while the Tutsi genocide in Rwanda took place during the civil war that broke out in this country. 2. If the Russian Caucasus Army was an obstacle to the criminal policy of genocide of the Armenian population of the Ottoman Empire, which during the hostilities on the Russian- Turkish front with the support of Armenian volunteer units occupied the provinces of Erzurum, Van, Bitlis in Western Armenia, as well as Trabzon. The complete extermination of the Tutsis in Rwanda was halted by the advance of their military formation, the Rwandan Patriotic Front (RWF), which managed to enter the capital, Kigali, to end the Houthi regime's criminal policy against the Tutsis. Unlike the RSF, the Armenian volunteer detachments in the Russian Caucasus Army did not act independently, they were not a military force capable of stopping the genocidal policy of the Ottoman Empire against the Armenian population. 3. The presence of the Russian Caucasus Army in some parts of Western Armenia, which was to some extent a guarantee of security for the genocidal Armenian population, as well as the Russian-Turkish front line, only temporarily stopped the continuation of the criminal policy of the Turkish authorities towards Armenians. During the revolutionary upheavals in Russia in 1917, the Russian Caucasian army was demoralized and disbanded, after which the Turkish authorities were able to continue the policy of the Armenian Genocide not only in the territories of Western Armenia formerly controlled by Russian troops, but also in Eastern Armenia and the Caucasus. The same can be said about Cilicia, when after the departure of the French troops, the Kemalists had the opportunity to continue the policy of genocide against the Armenians of Cilicia.